Kejadian Hipertensi di Wilayah Kerja Dinas Kesehatan - Trimansyah, Yuyun; Dwi Priyatno, Akhmad; Zaman, Chairil (Avicenna: Jurnal Ilmiah, 2025)
Background: Around 972 million people or 26.4% suffer from hypertension, this figure is likely to increase again. It is estimated that every year 9.4 million people die from hypertension and complications. All hypertension sufferers receive health services so that based on the 2022 profile table, it shows that the value of health service coverage for hypertension sufferers is 100%. The aim of this research is to find out a picture of the incidence of hypertension in the work area of ​​the Empat Lawang District Health Service. Method: The research design used was quantitative, with a cross sectional research design. The population in this study were all residents aged ≥ 15 years who lived in the work area of ​​the Empat Lawang District Health Service. The research was carried out in February-April 2024. Data analysis was carried out univariate and bivariate Results: Based on the results of the bivariate analysis, the variables were age (pvalue 0.013), knowledge (pvalue 0.040), smoking behavior (pvalue 0.048), and caffeine consumption (pvalue 0.035) Conclusion: There is a relationship between age, knowledge, smoking behavior and caffeine consumption with the incidence of hypertension Keywords: Hypertension, age, knowledge, smoking, caffeine